An injection locked millimeter-wave power amplifier with adaptive bias in 65 nm CMOS. (February 2016) - Xu, Leijun; Li, Qin; Pan, Tianhong; Bai, Xue
Abstract: A novel injection locked millimeter-wave power amplifier with adaptive bias (AB) is designed and presented. Based on the injection locked theory, the mechanism for injection locked amplifier is analyzed. To improve the linearity and efficiency, an injection locked power amplifier with AB is proposed for the first time, the bias and current source of the PA can be controlled by two envelope detectors that track the output power level. Fabricated in 65 nm CMOS, two Marchand baluns with center tap for DC bias are designed in the PA, the whole circuit occupies the area of 0.155 mm 2 . The measurement results show that the PA has the gain of 22.3 dB at 40.1 GHz. The output P 1 dB is 10.3 dBm which is better than that without AB. The maximum output power Psat is 13.3 dBm and the power-added efficiency (PAE) is 39.6%